Skier's posture estimation using real time kinematics GNSS measurements - Nemec, B.; Petric, T.; Supej, M. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
In this study we propose a solution based on generalization of skiing using back propagation neural networks (NN) and compare it with inverted pendulum based method. The reference measurement setup used for validation of both methods was a setup composed of inertial motion capture and GNSS measurement, respectively (Supej, 2010).